Don't die young : an anatomist's guide to your organs and your health. - Roberts, Alice, ....-; Grand, Ann, ....-; Hammond, Phil, ....- (London : Bloomsbury, 2007)
We're a nation of water cooler health experts - organic converts, proud of our supplements and detox herbal teas. But 87 per cent of us don't even know where our kidneys are. The time has surely come for us to get acquainted. In this fascinating tour of the human body, Dr Alice Roberts introduces us to our key organs, explaining their functions and idiosyncrasies in a style both ultimately informative and incredibly accessible. She explores the cells, the 'building blocks' of organs; the spongy pink lungs that turn grey as we grow older no matter where or how we live; the heart - alarmingly, heart-disease is the biggest killer in the UK; the stomach and intestines, with their precarious balance of churning acids; the liver and pancreas, much abused workers to break down the toxins we gleefully consume; the tireless and essential kidneys; the mysterious sex organs; the brain, the very centre of our selves; the skeleton and its amazing role in our evolution; and the skin, vigorously targeted by advertising companies and the organ that holds all of the others in. As well as (literally) delving into these organs, Alice discusses the latest research into what keeps them healthy, and gives us top tips for how to look after them. This is a glorious, dynamic and colourful combination of anatomy lesson and You Are What You Eat, and Alice Roberts is the perfect guide for this most intimate of journeys.
Keywords: Anatomie; Gezondheid; Gezondheidsleer; Interne geneeskunde